Pemanfaatan Tanaman Obat Keluarga Oleh Orang Tua Untuk Kesehatan Anak Di Duwet Ngawen Klaten - Susilo Yulianto; Agus Kirwanto (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Utilization of TOGA, Parent, Child Health. Medicinal Plants Family (TOGA) is an alternative treatment that has been carried out by the Indonesian people traditionally. The success of TOGA utilization is strongly influenced by the public's knowledge about the benefits of each type of medicinal plants, especially medicinal plants that have been studied empirically. It is also influenced by how the use of each of medicinal plants for a variety of different diseases. This study aims to determine the utilization of medicinal plants by parents for child health in Duwet, Ngawen, Klaten. This research method is descriptive, with a sample of 53 respondents were taken by simple random sampling technique. Data collection conducted direct interviews with respondents and open observation. The research instrument used was a questionnaire. The result showed that all respondents have ever used medicinal plants for their health. The conclusion of this study is the use of medicinal plants by parents for child health in Duwet, Ngawen, Klaten still needs to be improved further by providing the knowledge, awareness, willingness, and ability of the parents.